STUDENT’S STRATEGIES FOR REDUCING ANXIETY IN SPEAKING ENGLISH - Gantina, Audi; Rustandi, Andi; Rachmawati, Etika (UC Journal: ELT, Linguistics and Literature Journal, 2023)
Speaking is a communication activity that permits people to communicate verbally while using nonverbal cues from their bodies. Many students experience anxiety before speaking in front of a class, especially in English. The writer used five previous studies in this research. The purpose of this study is to identify the strategies and issues that students at Islamic Junior High School in Ciamis use to reduce anxiety when speaking English. This study used Likert scale instruments. This study used a qualitative approach, and for the design, it used a case study with 20 respondents. Meanwhile, the data of this study were analyzed by using descriptive statistics. Therefore, the writer proposes to study the causes of students' anxiety in English speaking and teachers' ways to alleviate anxiety in the classroom in the context of Indonesian TEFL. The study attempts to analyze "Students' Strategies for Reducing Speaking Anxiety in English". The result of this study overall shows that students felt fear in speaking English because of a lack of understanding of vocabulary, pronunciation, and grammar, The strategies they used are clustered around preparation, i.e., multiple speaking exercises.